Enhanced fracture resistance of thermoset/thermoplastic interfaces through crack trapping in a morphology gradient. (18th March 2021) - Voleppe, Quentin; Ballout, Wael; Van Velthem, Pascal; Bailly, Christian; Pardoen, Thomas
Abstract: The hybrid assembling of thermoplastics with thermosets through controlled interdiffusion is an attractive approach towards integrated structural composite bonding. The fracture toughness of the interphase between the high Tg thermoplastic polyetherimide and the RTM6 epoxy is found to be four times higher than the corresponding RTM6 value under specific curing cycle. The origin of this remarkable cracking resistance is elucidated by analyzing the crack path in relationship with the morphology and local elastoplastic and fracture properties of the interphase. The crack is trapped inside a morphological gradient involving a relatively low PEI concentration. Uniaxial compression and nanoindentation tests on homogenous blends exhibit an unexpected softening in this PEI content window. This efficient crack trapping mechanism originates thus from a synergistic coupling between a lower local strength and higher local fracture toughness. This finding opens to many new options for interface toughening beyond the system addressed in this research. Graphical abstract: Image 1 Highlights: Very high fracture toughness of co-cured RTM6 thermoset/PEI thermoplastic interphases. Toughening induced by presence of tough co-continuous region in the middle of the interphase. Cracking trapped in the co-continuous morphology due to softer behavior. Characterization of fracture surfaces, fracture mechanics and nanoindentation tests. Potential impact for application in composite bonding.